Infrared study of CO adsorption on alumina supported palladium particles - Libuda, Jörg; et al. (ELSEVIER SCIENCE BV, 1998)
We have studied the adsorption of CO on small palladium particles deposited on a well-ordered thin Al2O3 film on NiAI(110) using infrared reflection absorption spectroscopy (IRAS). Recent studies in our group with STM and SPA-LEED have shown that the deposited particles are predominantly terminated by (111)-type surfaces. The IR spectra exhibit several absorption bands, which are associated with linearly bound CO (2090-2120 cm(-1)) and bridge bonded CO (1930-1970 cm(-1)). On the larger, better ordered palladium aggregates another GO-induced band appears in the region of 1970-2000 cm(-1), which we assign to CO molecules bound on the edges of the particles. Evaporation of Pd in presence of a CO atmosphere leads to the formation of a palladium carbonyl-like compound which is stable only at low temperatures. The IR spectra of this species show apparent similarities with the spectra of CO on the small particles. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: aluminium oxide; carbon monoxide; clusters; infrared absorption spectroscopy; palladium